Safety and durability of the immune response after vaccination with the heterologous schedule of anti-COVID-19 vaccines SOBERANA®02 and SOBERANA® Plus in children 3–18 years old - Dagmar García-Rivera; Rinaldo Puga-Gómez; Sonsire Fernández-Castillo; Beatriz Paredes-Moreno; Yariset Ricardo-Delgado; Meiby Rodríguez-González; Carmen Valenzuela Silva; Rocmira Pérez-Nicado; Laura Rodríguez-Noda; Darielys Santana-Mederos; Yanet Climent-Ruiz; Enrique Noa-Romero; et al. (Vaccine: X)
Background: The heterologous three-dose schedule of the protein subunit anti-COVID-19 SOBERANA®02 and SOBERANA® Plus vaccines has proved its safety, immunogenicity and efficacy in pediatric population, but durability of immunogenicity is not yet dilucidated. This study reports the safety and durability of the humoral and cellular responses in children and adolescents 5–7 months after receiving the heterologous vaccine schedule of SOBERANA® 02 and SOBERANA® Plus. Methods: Children participating in a phase I/II clinical trial were followed-up for 5–7 months after the last dose. They were clinically examined by medical doctors, and their parents were interviewed searching for long-term adverse events. Blood samples were collected to evaluate the duration of humoral and cellular immune responses. Sera were tested for the presence of SARS-CoV-2 nucleocapsid (N) protein. Results: There were no reports of severe adverse events such as coagulation disorders, myocarditis, or pericarditis. None of the participants who withdrew from the trial during the follow-up period did so due to post-vaccination adverse events. The humoral response waned in time for N-negative children, but levels of specific and neutralizing antibodies remained similar to those attained after the second dose of SOBERANA® 02 in the heterologous schedule. Neutralizing antibodies against SARS-CoV-2 D614G and omicron BA.1 were detected 5–7 months post-vaccination. RBD-specific IFN-γ secreting cells showed no significant change compared to levels following primary immunization, in both N-negative and N-positive children. Conclusions: The vaccination regimen was safe over time, and both humoral and cellular immunity persisted in the vaccinated population aged 3–18 years, 5–7 months after receiving the heterologous SOBERANA® 02 and SOBERANA® Plus vaccine schedule.Trial registry: https://rpcec.sld.cu/trials/RPCEC00000374-En